The Formation of Networks in the Diaspora - Gil S. Epstein; Odelia Heizler (Cohen) (Institute for the Study of Labor (IZA), 2016)
In this paper, we examine possible types of network formation among immigrants in the diaspora and between those immigrants and the locals in different countries. We present the model by considering different possible interactions between immigrants and the new society in their host country. Spread of migrants from the same origin in the diaspora may well increase international trade between the different countries, depending on the types of networks formed. We present possible applications of network structure on the country of origin, such as on international trade. We find that when the size of the diaspora is sufficiently large, the natives in the different countries will be willing to bear the linking cost with the immigrants because the possible benefits increase with increasing size of the diaspora.
Keywords: D85; D74; J61; L14; 330; immigrants; networks; diaspora